Early Intervention for Children with Hearing Impairment in the South African Context: A Narrative Review of Legislative and Policy Frameworks - Luisa Petrocchi-Bartal; Katijah Khoza-Shangase; Amisha Kanji (Disabilities, 2025)
Globally, many countries have promulgated extensive, contextually relevant disability legislative policies for children with hearing impairment/d/Deafness (HI/d/D). The alignment of policies with their implementation, with robust monitoring, is essential for effective early intervention (EI) and early education (EE) outcomes. The study’s purpose was to review current South African EI and EE regulations, acts, and policies in relation to children with HI/d/D from birth to age six. An adapted Arksey and O’Malley framework with inductive thematic analysis was applied to synthesise and evaluate relevant information. Documentation was sourced between 1993 and 2023 from the official South African government portal and Google online searches using keywords. While 7976 documents were initially identified with the broad search and 1249 with a refined category search, only 17 met the specific inclusion criteria for policies referencing hearing impairment in early intervention and education. Seventeen documents were selected for study inclusion, with sixteen mentioning HI/d/D and multi-disciplinary, multi-sectoral, family-centred, culturally sensitive considerations superficially. One document from the Department of Health (DoH) specifically addressed early hearing detection and intervention (EHDI). Three main themes emerged, including Partnerships, Participation and Integration, Screening, Identification and/or Intervention, and Education/Special Education. Greater engagement with South African EI and education policies is essential to strengthen implementation, especially across sectors and at the community level. Mandating EHDI guidelines is critical to improving service delivery and ensuring smoother transitions between health, education, and social services for children with hearing impairment.